The Effectiveness of Problem-Based Learning At Primary Schools Toward The Mathematics Literacy Skills Reviewed From The Learning Styles And Genders - Abira, Abrar; Suyitno, Hardi; Latiana, Lita (Educational Management, 2021)
This research aims to find out how male and female learners' mathematics literacy skills with visual, auditory, and kinesthetic learning styles are. The applied research method was a mixed method. The applied strategy was a sequential explanatory. The population of this research consisted of the fifth graders of 023 Pekkabata Public Primary School in the academic year of 2019/2020. The applied sampling technique was purposive sampling. The sample was taken from one class. It was the Melati V class. The findings showed that (1) the learning applied by the problem-based learning model was effective toward the learners' mathematics literacy skills; (2) both male and female learners with visual learning styles met the seven indicators of mathematics literacy. They almost mastered all indicators. However, for male and female learners with auditory and kinesthetic learning style could not meet all mathematics literacy skill indicators but only several of the indicators.